Multipurpose Bottle / Noratiqah Umar … [et al.] - Umar, Noratiqah; Abdul Rahim, Hamizah; Khairul Nizam, Nurbatrisyia; Mohd Rosdi, Muhammad Naziirul; Shamson, Nur Syahindah Husna; Abdul Azis, Rafidah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
Every people require enough hydration, our MAGIC bottle will make your life more incredible. You can now own a premium bottle in the form of a functional, “MAGIC” bottle. With our patent bottle opener on the bottom, the durable powder paint and silicone sleeve keep MAGIC bottle looking fresh and feeling great in your hands. Then, screw-in lid prevents materials inside from spilling and inside insulated stainless-steel associated with neoprene to maintain the temperature of materials inside the bottle. What makes it different from another regular bottle is inside it is designed with many compartments to isolate different materials. There are three compartments where for the first compartment use to put water, second compartment using for powder mixture such as milo powder, coffee powder, milk powder, shaker powder and more, and the last compartments using to medicine or supplement. You can put the necessary medicines in it to avoid forgetting to take medicine. To make life easier and stylish with our designed multifunctional bottle. Here we can see, the goods produced can bring a lot of benefits, then the opportunity for commercial is high. This bottle is expected to provide assistance to consumers especially for those who are busy. This is because a person no longer must carry many containers at one time and able to save time and save space to place container.